Patients with refractory cytomegalovirus (CMV) infection following allogeneic haematopoietic stem cell transplantation are at high risk for CMV disease and non-relapse mortality. (December 2015) - Liu, J.; Kong, J.; Chang, Y.J.; Chen, H.; Chen, Y.H.; Han, W.; Wang, Y.; Yan, C.H.; Wang, J.Z.; Wang, F.R.; Chen, Y.; Zhang, X.H.; et al.
Abstract: Pre-emptive therapy is an effective approach for cytomegalovirus (CMV) control; however, refractory CMV still occurs in a considerable group of recipients after allogeneic haematopoietic stem cell transplantation (allo-HSCT). Until now, hardly any data have been available about the clinical characteristics and risk factors of refractory CMV, or its potential harmful impact on the clinical outcome following allo-HSCT. We studied transplant factors affecting refractory CMV in the 100 days after allo-HSCT, and the impact of refractory CMV on the risk of CMV disease and non-relapse mortality (NRM). We retrospectively studied 488 consecutive patients with CMV infection after allo-HSCT. Patients with refractory CMV in the 100 days after allo-HSCT had a higher incidence of CMV disease and NRM than those without refractory CMV (11.9% vs. 0.8% and 17.1% vs. 8.3%, respectively). Multivariate analysis showed that refractory CMV infection in the 100 days after allo-HSCT was an independent risk factor for CMV disease (hazard ratio (HR) 10.539, 95% CI 2.467–45.015, p 0.001), and that refractory CMV infection within 60–100 days after allo-HSCT was an independent risk factor for NRM (HR 8.435, 95% CI 1.511–47.099, p 0.015). Clinical factors impacting on the risk of refractory CMV infection included receiving transplants from human leukocyte antigen-mismatched family donors (HR 2.012, 95% CI 1.603–2.546, p <0.001) and acute graft-versus-host disease (HR 1.905, 95% CI 1.352–2.686, p <0.001). We conclude that patients with refractory CMV infection during the early stage after allo-HSCT are at high risk for both CMV disease and NRM.